Primary scrotal Paget’s disease: a case report and literature review - Liang, Pinyao; Zhang, Junfeng; Xie, Xiaofeng; Wang, Yumin; Li, Junxiong; Qin, Jingbo; Gu, Peng; Liu, Xiaodong (Frontiers in Medicine, 2026)
ObjectiveThe objective of the study was to report a case of primary scrotal Paget’s disease and discuss its clinical characteristics, diagnosis, and management based on the literature.MethodsThe clinical data of a patient with primary scrotal Paget’s disease admitted to the Second Department of Urology at the First Affiliated Hospital of Kunming Medical University in December 2024 were retrospectively analyzed.ResultsThis is a case report of a 58-year-old man who presented with erythema on the left penile root and scrotum persisting for over 6 months. Histopathological examination of the skin lesion confirmed extramammary Paget’s disease. He underwent wide local excision under general anesthesia. The surgery was successful, resulting in negative surgical margins. Postoperative adjuvant radiotherapy was administered due to the diffuse nature of the lesion boundaries. The patient tolerated the treatment well, recovered favorably, and is currently on a scheduled follow-up regimen with no evidence of recurrence to date.ConclusionThe early clinical manifestations of scrotal Paget’s disease resemble chronic dermatoses. Early diagnosis and exclusion of metastatic disease or underlying internal malignancies are crucial. The primary treatment is wide local excision, with radiotherapy serving as adjuvant therapy post-surgery.